Evaluating DOAC dipstick testing in the management of acute stroke: protocol for a multicentre, prospective, observational registry study - Philip Choi; Helen Dewey; Edward Patrick Callaly; Peter Shuangyue Tan; Emily Schembri; Marija Borosak (BMJ Open)
Introduction Direct oral anticoagulants (DOACs) are preferred over vitamin K antagonists for stroke prophylaxis in non-valvular atrial fibrillation. Yet, DOAC use is regarded as a contraindication for intravenous thrombolysis in acute ischaemic stroke. The stratification of patients into ‘on-therapy’ and ‘off-therapy’ categories based on their plasma DOAC concentrations is particularly crucial in the acute phase of stroke when decisions for thrombolysis or anticoagulation reversal are time-sensitive. The novel point-of-care DOAC dipstick assay (DOASENSE) rapidly assesses urine for clinically significant DOAC levels, potentially broadening eligibility for thrombolysis or targeted reversal therapy. This multicentre prospective observational registry study aims to evaluate the accuracy and clinical utility of DOAC dipstick testing compared with plasma DOAC assays in acute stroke management across regional Australian hospitals.Methods and analysis This multicentre, prospective, observational study will enrol participants presenting to hospitals across Victoria and Tasmania with acute ischaemic stroke or intracerebral haemorrhage with DOAC ingestion within 48 hours of presentation. Plasma DOAC concentrations measured by chromogenic assays will be compared with rapid urine dipstick results from DOASENSE testing. There is a target sample size of 146 participants. The primary outcomes are as follows: (1) proportion of ischaemic stroke participants with off-therapy plasma DOAC levels and (2) eligibility for reperfusion therapy based on DOASENSE and plasma DOAC concentrations. Secondary outcomes are follows: (1) ischaemic stroke aetiology for participants with on-therapy vs off-therapy DOAC levels; (2) proportion of participants meeting criteria for pharmacological DOAC reversal based on DOASENSE outcomes; (3) incidence of false-negative and false positive DOASENSE results in clinically significant DOAC plasma concentrations at a threshold of ≥30 ng/mL and (4) an exploratory analysis of any false negative DOASENSE assays to identify potential contributing factors.Ethics and dissemination Ethics approval has been granted by the Eastern Health Human Research Ethics Committee (reference number: 99628). Dissemination of findings will occur through peer-reviewed publications and academic conferences.